2011
DOI: 10.1007/s10384-011-0101-8
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of trabeculectomy blebs with Visante anterior segment optical coherence tomography after digital ocular compression

Abstract: Digital ocular compression may be useful in maintaining bleb morphology when it is used for 6 months postoperatively. Response to ocular compression as assessed by bleb morphology was different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
(28 reference statements)
0
9
0
1
Order By: Relevance
“…Bleb avascularity often causes the bleb wall to be thin and brittle [2,7,24,25]. Therefore, noncontact meibography was performed using a mobile, pen-shaped meibography device (Meibom Pen; Japan Focus Co., Tokyo, Japan) after the upper and lower eyelids had been inverted to avoid compression of the blebs.…”
Section: Evaluation Of Meibomian Gland Morphologymentioning
confidence: 99%
“…Bleb avascularity often causes the bleb wall to be thin and brittle [2,7,24,25]. Therefore, noncontact meibography was performed using a mobile, pen-shaped meibography device (Meibom Pen; Japan Focus Co., Tokyo, Japan) after the upper and lower eyelids had been inverted to avoid compression of the blebs.…”
Section: Evaluation Of Meibomian Gland Morphologymentioning
confidence: 99%
“…Anterior segment optical coherence tomography (OCT) has often been used to observe the anterior ocular segment [6,7]. Therefore, the aim of our preliminary study was to consider the potential impact of scleral shape on the outcome of trabeculectomy.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of our findings we speculate that bleb size and bleb wall thickness are indicative of a failing bleb. Ultrasound biomicroscopy and anterior segment optical coherence tomography have shown that bleb size, intra-bleb structure, and intra-bleb reflectivity are closely associated with bleb function [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of the filtering bleb, however, is suspected to contribute to uncontrolled IOP in most cases, because inflammatory reactions at the bleb site cause vasodilation, production of inflammatory cytokines, and other problems, resulting in fibrosis at and around the filtering bleb [8,9]. It is well known that bleb morphology is highly correlated with IOP control [10,11], and that bleb size and intra-bleb reflectivity have predictive value for IOP after filtering surgery.…”
Section: Introductionmentioning
confidence: 99%